Pemaknaan Stiker Whatsapp untuk Menanggapi Obituari dari Sudut Pandang Kesantunan Berbahasa - Keni Suantini (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Obituaries are one of the information that is often conveyed, especially in the Whatsapp application media. Delivering an obituary is even recommended in Islam and a response in the form of expressions of condolences also accompanies this recommendation. However, a phenomenon occurred in the form of using stickers in expressions of condolences. This gives rise to different views about whether it is polite or not. This study aims to analyze the meaning of the condolence sticker from the point of view of language politeness by using a qualitative descriptive method. From the point of view of semiotics, the use of stickers to convey condolences has fulfilled the function of communication. Meanwhile, according to politeness theory, this is not justified. The majority of scholars also consider the use of stickers to convey condolences is also a waste of time.